Bentuk Tabu Bahasa Korea - Anak Agung Gede Suhita Wirakusuma (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2020)
This research was condutcet with the aim of knowing kind of taboo in Korean language. This research is a qualitative research using observation and interview methods in data collection against Koreans who are living and settling in Bali. This research focused on verbal taboo. Classification of Taboo in Korean using theory of taboo from Frazer (1955). Research findings and analysis result show that taboo in Korean has variety depending on the context of the situation and the interlocutor.